2013
DOI: 10.1523/jneurosci.2516-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Morphine Exposure Affects Long-Term Microglial Function and Later-Life Relapse Liability in a Model of Addiction

Abstract: Adolescence in humans represents a unique developmental time point associated with increased risk-taking behavior and experimentation with drugs of abuse. We hypothesized that exposure to drugs of abuse during adolescence may increase the risk of addiction in adulthood. To test this, rats were treated with a sub-chronic regimen of morphine or saline in adolescence, and their preference for morphine was examined using conditioned place preference (CPP) and drug-induced reinstatement in adulthood. The initial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 28 publications
(41 reference statements)
6
67
1
Order By: Relevance
“…reward due to alcohol. It is postulated that long-term changes in microglial function are important in relapse of drug seeking behavior [32]. Notably, glial cells are activated by drugs of abuse and morphine-induced pro-inflammatory glial activation alters neuronal excitability and synaptic connectivity, opposes morphine-induced withdrawal, and reward to morphine [21].…”
Section: Discussionmentioning
confidence: 99%
“…reward due to alcohol. It is postulated that long-term changes in microglial function are important in relapse of drug seeking behavior [32]. Notably, glial cells are activated by drugs of abuse and morphine-induced pro-inflammatory glial activation alters neuronal excitability and synaptic connectivity, opposes morphine-induced withdrawal, and reward to morphine [21].…”
Section: Discussionmentioning
confidence: 99%
“…Morphine also upregulates chemokines and activates glial cells in the brain (24), and these activations might be based on CCL2. Psychic dependence on methamphetamine or morphine was attenuated by agents that suppress the activity of microglia and astrocytes, such as minocycline or ibudilast (30,31). We previously reported that behavioral sensitization to methamphetamine was improved by peroxisome proliferator-activated receptorg agonists, being suppressive agents for inflammatory macrophages and microglia (32).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic administration of ibudilast inhibits ethanol (Bell et al, 2015) and methamphetamine intake (Snider et al, 2013), sensitization of the locomotor response to methamphetamine (Snider et al, 2012), as well as stress-and drug-primed reinstatement of methamphetamine seeking (Beardsley et al, 2010). Ibudilast also reduces morphine withdrawal and CPP, likely as a result of its ability to reduce morphine-induced dopamine release in the NAc (Rolan et al, 2009;Schwarz and Bilbo, 2013). Although ibudilast treatment has a variety of effects that could be beneficial in the pharmacological treatment of addiction, it has yet to be determined whether inhibition of PDE activity, inflammation, or neurotrophic factor release is responsible for its effects on the inhibition of drugseeking and drug-related behaviors.…”
Section: G Glial Modulatorsmentioning
confidence: 99%